Reactivity of 4-Pyrimidyl Sulfonic Esters in Suzuki-Miyaura Cross-Coupling Reactions in Water Under Microwave Irradiation - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Rodríguez-Aguilar, J; Aburto-Bernal, I (John Wiley and Sons Inc, 2021)
The reactivity of four 4-pyrimidyl sulfonic esters in Palladium-catalyzed Suzuki–Miyaura cross-coupling reactions was studied with various boronic acids. All the reactions were conducted in water under microwave irradiation. Electron-rich aryl boronic acids exhibited higher yields when triflate (−OSO2CF3) was used as the pseudohalide, whereas electron-poor aryl boronic acids reacted faster when nonaflate was employed (−OSO2(CF2)3CF3). Furthermore, the reactivity guide for Pd-catalyzed coupling of these accessible pseudohalides with boron-based coupling partners was applied to synthesize a bipyrimidine in excellent yield. Finally, the 2-methylpyrimidines obtained are suitable starting materials for the synthesis of luminescent sensors. © 2021 Wiley-VCH GmbH